ASSESSMENT OF STUDENT DISCIPLINARY MEASURES ADMINISTERED BY SECONDARY SCHOOL AUTHORITIES IN BUNGOMA EAST SUB-COUNTY, KENYA - Wekesa, Wafula Sammy; Lwangale, David Wafula; Ngome, Prof. Charles K. (IJRDO - Journal of Applied Management Science, 2016)
The study assessed student disciplinary measures administered by secondary school authorities in Bungoma East Sub-County, Kenya. The study adopted descriptive survey design and mainly targeted learners who stayed mainly under the care of guardians instead of their real parents as well as learners who had parents but such parents that never attended to their school issues. Simple random sampling was used to select 4 schools from the 35 schools in the Sub-County. From the 4 schools, 4 guidance and counseling masters; 4 HOD’s in charge of discipline, and 4 principals were purposively sampled for the study. Thereafter, a 10% of learners with indiscipline cases per school were purposefully selected. A similar number of learners who enjoyed full parental care at all levels were randomly selected for comparison purposes. Data was analyzed using descriptive statistics, specifically use of percentages and frequencies. The study established that corporal punishment was cherished by schools. This was attributed to the belief that it is biblically directed that sparing the rod spoils the child. It was also owed to experience where corporal punishment had been seen to control bad behavior. However, this was against the government’s directive on ban of corporal punishment. Manual work should be used as form of punishment. Apart from being a form of punishment, manual work is important in training children to do physical work. Suspension from school was also used as a disciplinary measure. However, expulsion was refuted.